Chicago's New Negroes : Modernity, the Great Migration, and Black Urban Life - Baldwin, Davarian L. (Book collections on Project MUSE., 2007)
As early-twentieth-century Chicago swelled with an influx of at least 250,000 new black urban migrants, the city became a center of consumer capitalism, flourishing with professional sports, beauty shops, film production companies, recording studios, and other black cultural and communal institutions. Davarian Baldwin argues that this mass consumer marketplace generated a vibrant intellectual life and planted seeds of political dissent against the dehumanizing effects of white capitalism. Pushing the traditional boundaries of the Harlem Renaissance to new frontiers, Baldwin identifies a fresh.